Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Sure! Let's evaluate the function [tex]\( f(x) = x^2 - 4 \)[/tex] at the given points step-by-step.
(a) To find [tex]\( f(3) \)[/tex]:
1. Substitute [tex]\( x = 3 \)[/tex] into the function [tex]\( f(x) \)[/tex].
2. [tex]\( f(3) = 3^2 - 4 \)[/tex]
3. Calculate the square: [tex]\( 3^2 = 9 \)[/tex]
4. Subtract 4 from 9: [tex]\( 9 - 4 = 5 \)[/tex]
Thus, [tex]\( f(3) = 5 \)[/tex].
(b) To find [tex]\( f(-4) \)[/tex]:
1. Substitute [tex]\( x = -4 \)[/tex] into the function [tex]\( f(x) \)[/tex].
2. [tex]\( f(-4) = (-4)^2 - 4 \)[/tex]
3. Calculate the square: [tex]\( (-4)^2 = 16 \)[/tex]
4. Subtract 4 from 16: [tex]\( 16 - 4 = 12 \)[/tex]
Thus, [tex]\( f(-4) = 12 \)[/tex].
(c) To find [tex]\( f(0) \)[/tex]:
1. Substitute [tex]\( x = 0 \)[/tex] into the function [tex]\( f(x) \)[/tex].
2. [tex]\( f(0) = 0^2 - 4 \)[/tex]
3. Calculate the square: [tex]\( 0^2 = 0 \)[/tex]
4. Subtract 4 from 0: [tex]\( 0 - 4 = -4 \)[/tex]
Thus, [tex]\( f(0) = -4 \)[/tex].
(d) To find [tex]\( f(-2) \)[/tex]:
1. Substitute [tex]\( x = -2 \)[/tex] into the function [tex]\( f(x) \)[/tex].
2. [tex]\( f(-2) = (-2)^2 - 4 \)[/tex]
3. Calculate the square: [tex]\( (-2)^2 = 4 \)[/tex]
4. Subtract 4 from 4: [tex]\( 4 - 4 = 0 \)[/tex]
Thus, [tex]\( f(-2) = 0 \)[/tex].
Summarizing the results:
- [tex]\( f(3) = 5 \)[/tex]
- [tex]\( f(-4) = 12 \)[/tex]
- [tex]\( f(0) = -4 \)[/tex]
- [tex]\( f(-2) = 0 \)[/tex]
(a) To find [tex]\( f(3) \)[/tex]:
1. Substitute [tex]\( x = 3 \)[/tex] into the function [tex]\( f(x) \)[/tex].
2. [tex]\( f(3) = 3^2 - 4 \)[/tex]
3. Calculate the square: [tex]\( 3^2 = 9 \)[/tex]
4. Subtract 4 from 9: [tex]\( 9 - 4 = 5 \)[/tex]
Thus, [tex]\( f(3) = 5 \)[/tex].
(b) To find [tex]\( f(-4) \)[/tex]:
1. Substitute [tex]\( x = -4 \)[/tex] into the function [tex]\( f(x) \)[/tex].
2. [tex]\( f(-4) = (-4)^2 - 4 \)[/tex]
3. Calculate the square: [tex]\( (-4)^2 = 16 \)[/tex]
4. Subtract 4 from 16: [tex]\( 16 - 4 = 12 \)[/tex]
Thus, [tex]\( f(-4) = 12 \)[/tex].
(c) To find [tex]\( f(0) \)[/tex]:
1. Substitute [tex]\( x = 0 \)[/tex] into the function [tex]\( f(x) \)[/tex].
2. [tex]\( f(0) = 0^2 - 4 \)[/tex]
3. Calculate the square: [tex]\( 0^2 = 0 \)[/tex]
4. Subtract 4 from 0: [tex]\( 0 - 4 = -4 \)[/tex]
Thus, [tex]\( f(0) = -4 \)[/tex].
(d) To find [tex]\( f(-2) \)[/tex]:
1. Substitute [tex]\( x = -2 \)[/tex] into the function [tex]\( f(x) \)[/tex].
2. [tex]\( f(-2) = (-2)^2 - 4 \)[/tex]
3. Calculate the square: [tex]\( (-2)^2 = 4 \)[/tex]
4. Subtract 4 from 4: [tex]\( 4 - 4 = 0 \)[/tex]
Thus, [tex]\( f(-2) = 0 \)[/tex].
Summarizing the results:
- [tex]\( f(3) = 5 \)[/tex]
- [tex]\( f(-4) = 12 \)[/tex]
- [tex]\( f(0) = -4 \)[/tex]
- [tex]\( f(-2) = 0 \)[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.